Genome-Wide Association Analysis Reveals Key Genes Responsible for Egg Production of Lion Head Goose - Zhao, Qiqi; Chen, Junpeng; Zhang, Xinheng; Xu, Zhouyi; Lin, Zhenping; Li, Hongxin; Lin, Wencheng; Xie, Qingmei (Frontiers in Genetics, 2020)
The lion head goose is one of the most important agricultural resources in China; however, its breeding process is relatively slow. In the present study, a genome-wide association study was performed for the genetic selection of egg production characters in lion head geese. We detected 30 single-nucleotide polymorphisms located in or near 30 genes that might be associated with egg production character, and quantitative real-time polymerase chain reaction was used to verify their expression level in lion head geese. The results showed that the expression levels of CRTC1 (encoding CREB-regulated transcription coactivator 1), FAAH2 (encoding fatty acid amide hydrolase 2), GPC3 (encoding glypican 3), and SERPINC1 (encoding serpin family C member 1) in high egg production population were significantly lower than those in the low egg production populations (*P < 0.05). The expression levels of CLPB (encoding caseinolytic peptidase B protein homolog), GNA12 (encoding guanine nucleotide-binding protein subunit alpha-12), and ZMAT5 (encoding zinc finger, matrin type 5) in the high egg production population were significantly higher than those in the low egg production populations (*P < 0.05). The expression of BMP4 (encoding bone morphogenetic protein 4), FRMPD3 (encoding FERM and PDZ domain containing 3), LIF (encoding leukemia inhibitory factor), and NFYC (encoding nuclear transcription factor Y subunit gamma) in the high egg production population were very significantly lower than those in the low egg production population (**P < 0.01). Our findings provide an insight into the economic traits of lion head goose. These candidate genes might be valuable for future breeding improvement.